The Role-Playing Counseling to Improve Knowledge about Risky Sexual Behavior of Adolescents at SMAN 1 Kupang - Bengu, Herfyn Jelita; Limbu, Ribka; Takaeb, Afrona E. L. (Timorese Journal of Public Health, 2020)
Risky adolescent sexual behavior can be caused reproductive health problems in adolescents such as unwanted pregnancy, sexually transmitted diseases, and abortion. To increase knowledge about reproductive health, health education is needed. One of the health education methods that can be used in small group education methods is role-playing.This study aims to determine the impact of health education using role-playing methods to improve the knowledge about risky sexual behavior in class XII adolescents in SMAN 1 Kupang. The research method used was a pre-experiment one-group pre-test post-test design. The sampling technique used was purposive sampling and the samples obtained included 88 people. The obtained data were analyzed by the T-test. The results of this study suggest that role-play health education raises the knowledge of SMA Negeri 1 Kupang students about sexual behavior in adolescents before and after counseling with role-play methods with a significance value (ρ) of 0.00 <(α) 0.05. The role-play method can be used as a method to provide counseling for teenagers.